Prevalence and Risk Factors of Malnutrition Among Adult Cancer Patients in Outpatient Clinic at Cancer Center: A Cross-sectional Study - Jongpairat, Piangpen; Thengwatthanachote, Nicharee; Unhapipatpong, Chanita; Mitpracha, Manoon; Julanon, Narachai (Journal of The Department of Medical Services, 2025)
Background: Cachexia is a common issue among cancer patients. Nutritional assessments and awareness of the risk factors for malnutrition should be prioritized. Objectives: This study aimed to investigate the prevalence of malnutrition among adult cancer patients in the cancer center using the validated Nutrition Alert Form (NAF). The secondary objective was to evaluate the risk factors of malnutrition among adult cancer patients. Moreover, the aim is to find correlations among NAF, laboratory findings, and anthropometric parameters. Methods: We conducted a cross-sectional study involving 272 outpatients with cancer at the Cancer Center, Khon Kaen Hospital, from October 2022 to August 2023. Nutritional status was assessed using the NAF, and risk factors including baseline characteristics, anthropometric indices, laboratory results, and cancer-related factors were evaluated. Results: Among the 272 patients, the median age was 59 years (IQR 51-67) and the median BMI was 21.7 kg/m2 (IQR 19.2-24.8). The prevalence of moderate and severe malnutrition, according to NAF-B and NAF-C, was 43.8% and 11.8%, respectively. Patients with severe malnutrition experienced significant weight loss compared to those without malnutrition (% of weight change -12.77% vs. -2.13%, p < .001). Factors significantly associated with malnutrition included age ≥ 60 years old and BMI < 20 kg/m2 (Adjusted odds ratio (adjOR) 2.17, (95%CI: 1.15, 4.12); and adjOR 3.97 (95%CI: 1.93, 8.17)) respectively. There was a highly significant correlation among NAF. Conclusion: The prevalence of malnutrition among outpatients with cancer is high. NAF can effectively evaluate nutritional status. Significant risk factors include low BMI and being elderly.